ANALISIS PENGARUH RISIKO SISTEMATIS DAN LIKUIDITAS TERHADAP TINGKAT PENGEMBALIAN SAHAM: STUDIPADA PERBANKAN DI INDONESIA - , David, Dr. Khomsiyah, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This empirical study analyzes the effect of systematic risk and stock liquidity on stock returns by studies on banking in Indonesia. Banking sector in Indonesia Stock Exchange will be use as the data population of this thesis, which obtained by using purposive sampling method. This research is using secondary data including the banking sector, stock prices, and daily trading volume on the stock exchange January 2011 until December 2012, and as a proxy of stock returns is financial sector composite index in the period 2011 to 2012. This research use linear regression analysis by ordinary least square (OLS) method. Classical assumption test shows all the data has fulfilled the classical assumptions requirements, and testing the linear regression model has concluded systematic risk and liquidity affects stock returns banking sector simultaneously, but partially only stock liquidity has significant effect on the stock returns of banking sector.